Inteligência emocional e sua relação com as variáveis profissionais estresse no trabalho, adaptabilidade de carreira e autoeficácia ocupacional - Ferrari, Isabela Sbravatti (2020)
Emotional Intelligence (EI) corresponds to the ability to perceive, facilitate thought, understand and manage emotions and has been related to several factors in life - such as work. This research aimed to verify relations between EI and professional variables: work stress, career adaptability and occupational self-efficacy of adults in the labor market, using the Emotional Intelligence Battery, Work Stress Scale, Career Adaptability Scale, Occupational SelfEfficacy Scale and a Socioeconomic Questionnaire. The sample consisted of 62 participants, aged between 20 and 65 years old (average=31,8; sd=9,67; median=29,5), of both sexes with slight predominance of men (51,6%; n=32), civil servants (11,3%, n=7), private workers (51,6%, n=32), service providers (27,4%, n=17) or informal/temporary workers (9,7%, n=6). For the sample of this study, it was possible to observe that the general emotional intelligence was not related to the variables work stress, career adaptability and occupational self-efficacy. The first factor of perception of emotions itself was negatively and strongly correlated with work stress, it was also positively and moderately correlated with factors 2 (control), 4 (confidence) and general of career adaptability. The second factor of Understanding Emotions – referring to the understanding of emotional transitions, the total score of the Understanding Emotions test and the second factor of Regulation of Emotions – referring to the use of ineffective strategies – correlated with factor 1 (concern) of career adaptability, the first two being positive and moderate and the last negative and moderate. No EI factor correlated with occupational self-efficacy. Although none of the correlational hypotheses proposed in this research - between emotional intelligence (and its factors) and stress at work, career adaptability and occupational self-efficacy - has been verified, with only the listed correlations for the total sample, further exploration of the data shows that some EI variables correlated with professional variables for specific populations. The multiple regression analysis showed, in addition, that work stress and participants’ age appeared negatively, and the career-adaptability (CA) control factor, positively, as predictors of perceiving own emotions. Age and professional situation were negative and positive predictors, respectively, of the performance in understanding emotions, while the CA factors concern (F1), control (F2) and curiosity (F3) predicted the emotional regulation of the participants - negatively the CA- F1 and positively both CA-F2 and CA-F3. Thus, different contexts and other variables may play some role in the possible relationships between EI and the three professional variables investigated here.